Pengaruh jenis inokulum Aspergillus niger, Saccharomyces cereviseae dan lama fermentasi terhadap komposisi nutrisi ampas Putak (Corypha gebanga) - Daniel Soares; Irfan H. Djunaidi; Muhammad Halim Natsir (Faculty of Animal Science, Universitas Brawijaya, 2018)
The experiment was to determine the composition of putak waste nutrein to increase through fermentation by Aspergillus niger, Saccharomyces cereviseae and its combinations. The experiment method used laboratory experimental method by applying Nested Plot Random Design. The first factor is inoculum (P): Aspergillus niger, Saccharomyces cereviseae and their combination on the level of 1,5% and the incubation time length (W): 0, 24, 48, 72 hours as the second factor. Variables measured of putak waste fiber component analysis. The results showed that the type of inoculum effect on fiber component (Neutral Detergent Fiber / NDF, Hemicellulose and Lignin) is very significantly influence (P<0,01) and fiber component (Acid Detergent Fiber/ADF and Cellulose) is significantly influence (P<0,05), while the incubation time showed very significantly influence (P<0,01) to the fiber component (NDF) and not significantly influence (P>0,05) to ADF, Hemicellulose, Cellulose and Lignin.